Parsonage-Turner Syndrome After COVID-19 Vaccination: A Case Report. Issue 2 (25th April 2022) - Ghanta, Ramesh B.; Karistinos, Anastassios; Atassi, Omar H.
Abstract : Case: One week after receiving a COVID-19 vaccine in his left deltoid, a 34-year-old man developed severe right periscapular pain that lasted 2 weeks and was followed by profound right shoulder girdle atrophy and weakness. Both the pain and motor deficits resolved over the subsequent 4 months. Conclusion: Parsonage-Turner syndrome (PTS) is an idiopathic brachial plexopathy that can develop in the setting of recent vaccination and lead to significant shoulder pain and weakness. Given the worldwide increase in newly vaccinated patients, orthopaedic surgeons should take detailed histories to identify potential triggers (recent vaccination or illness) that point toward PTS rather than musculoskeletal pathology.